2013
DOI: 10.3329/akmmcj.v4i2.16938
|View full text |Cite
|
Sign up to set email alerts
|

Isolation of Bacteria Causing Urinary Tract Infections and their Antibiotic Susceptibility Profile at Anwer Khan Modern Medical College Hospital

Abstract: Among hospitalized patients, the most common nosocomial infection is Urinary tract infection (UTI). The knowledge about the type of pathogens responsible for UTI and susceptibility and resistance pattern of the causative agents at a specific area may help the doctors to choose correct treatment regimen. This study was aimed to investigate the antibiotic susceptibility and resistance pattern of isolated urinary pathogens. This study was done at Anwer Khan Modern Medical College Hospital, Dhaka during January- J… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
7
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 7 publications
3
7
1
Order By: Relevance
“…Majority (92.4%) of Enterobacteriaceae isolates were found to be MDR. This finding is comparable to Shilpi et al [18] in Bangladesh who has found that members of Enterobacteiacaee variably sensitive to different antibiotics. Similar susceptibility pattern was also reported by Sultana et al [19] The overall prevalence of MDR among enterobacteriaceae isolates identified from patients with symptomatic UTI was 92.4% which is similar with the results from previous study in Gondar (85.5%), Eshetie (87.4%) and Mozambique (88.2%) [20,21,22] while it was higher than reports from other study in Ethiopia: Gondar (68%), and Dessie (74.6%) [23,24] and many other countries, such as USA (19.1%), Belgium (62%), and Italy (62%), Nepal (40.1%, 64.04%).…”
Section: Discussionsupporting
confidence: 88%
“…Majority (92.4%) of Enterobacteriaceae isolates were found to be MDR. This finding is comparable to Shilpi et al [18] in Bangladesh who has found that members of Enterobacteiacaee variably sensitive to different antibiotics. Similar susceptibility pattern was also reported by Sultana et al [19] The overall prevalence of MDR among enterobacteriaceae isolates identified from patients with symptomatic UTI was 92.4% which is similar with the results from previous study in Gondar (85.5%), Eshetie (87.4%) and Mozambique (88.2%) [20,21,22] while it was higher than reports from other study in Ethiopia: Gondar (68%), and Dessie (74.6%) [23,24] and many other countries, such as USA (19.1%), Belgium (62%), and Italy (62%), Nepal (40.1%, 64.04%).…”
Section: Discussionsupporting
confidence: 88%
“…In current study, it was seen that, 57% of E. coli and 62.5% of K. pneumoniae were positive for ESBL. This frequency is much higher than previous four reports from Bangladesh 5,6,13,14 . ESBL positive organisms are also increasingly being identified in Korea 15 and USA 16 .…”
Section: Resultscontrasting
confidence: 66%
“…In two different reports from Dhaka, Bangladesh, patients suffering from UTI were of much lower age, but patients having infections due to ESBL positive organisms had a mean age of 71 years in Spain 6,9,13 . In current study, it was seen that, 57% of E. coli and 62.5% of K. pneumoniae were positive for ESBL.…”
Section: Resultsmentioning
confidence: 99%
“…This frequency is much higher than previous four reports from Bangladesh. 5,6,9,10 ESBL positive organisms are increasing in Korea and USA. Limitations of the study The study duration was short and sample size was small.…”
Section: Discussionmentioning
confidence: 99%